Borehole Inner Surface Visualization System with Vibration Cancellation and Trajectory Smoothing Based on Optical Monocular Video Camera - Zong, Nan; Al-Nuaimy, Waleed; Worthington, Paul (SN computer science, 2025)
The rapid digitization and modeling of the planet brings with it increased demand for the tools necessary to process and visualize disparate streams of multivariate and often highly complex geophysical data. However, more complicated the detection system is, less reliability can it guarantees. In order to addresses the challenge of visual reconstruction of the geometry of the inner surface of a borehole from video data collected via a simple monocular optical camera detector, We introduce a novel system of algorithms to unwrap the cylindrical borehole inner surface data, to compensate for the offsets and errors arising during data acquisition and finally to remap physical depth of pixels with time based video data. For unwrapping and compensation, three modules are designed: unwrapping module to generate visualization results of borehole inner surfaces; Vibration cancellation module that compensates for rotation and drift errors meanwhile balancing computational cost and performance; Trajectory smoothing based on image convolution signal processing methods to filter out anomalies and interruptions that arise as a result of the other processing stages. For physical depth estimation of pixels, two works are implemented: General time to depth matching using video frame time index and distance of released cable recorded by winch rotary encoder; Estimation of distances between pixels and detector on a single frame modeled by the relationship between radius of boreholes and the visual deformation on camera image of the points positions on the borehole surface. The proposed system integrates these modules to generate planar side-view images with a high level of spatial accuracy. It also contributes to establish a novel and easy-to-access visualization tool of boreholes with simplified detectors that only consists of a monocular camera and a fixed circular LED band. Results has demonstrated the system is capable of resisting high frequency drift and the effects of rotation and vibrations in harsh subterranean environments, and performs well in remapping the depth of pixels on the inner surface from time-based distance to physical distance. This novel combination of image processing methods marks a significant improvement over currently published borehole video exploration techniques, and can be further extended and enhanced to deliver more accurate multi-sensor 3D modeling and reconstruction of the complex inner structure of geophysical boreholes.